2001
DOI: 10.1126/science.1060152
|View full text |Cite
|
Sign up to set email alerts
|

A Silent Slip Event on the Deeper Cascadia Subduction Interface

Abstract: Continuous Global Positioning System sites in southwestern British Columbia, Canada, and northwestern Washington state, USA, have been moving landward as a result of the locked state of the Cascadia subduction fault offshore. In the summer of 1999, a cluster of seven sites briefly reversed their direction of motion. No seismicity was associated with this event. The sudden displacements are best explained by approximately 2 centimeters of aseismic slip over a 50-kilometer-by-300-kilometer area on the subduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
777
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 857 publications
(816 citation statements)
references
References 23 publications
33
777
1
5
Order By: Relevance
“…Similar seismic signals have been recently observed in the Cascadia subduction zone. Here periods of deep tremor are clearly correlated both in space and time with the slip episodes observed every 14 ± 2 months by continuous GPS measurement on Vancouver Island and northern Washington [Dragert et al, 2002;Rogers and Dragert, 2003;McCausland and Malone, 2003]. Data from the widely-spaced stations of the Pacific Northwest Seismic Network (PNSN) have been used to infer rough estimates about the source location, using either the signal's envelopes [McCausland and Malone, 2004] or a modified beam-forming technique [Kao and Shan, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Similar seismic signals have been recently observed in the Cascadia subduction zone. Here periods of deep tremor are clearly correlated both in space and time with the slip episodes observed every 14 ± 2 months by continuous GPS measurement on Vancouver Island and northern Washington [Dragert et al, 2002;Rogers and Dragert, 2003;McCausland and Malone, 2003]. Data from the widely-spaced stations of the Pacific Northwest Seismic Network (PNSN) have been used to infer rough estimates about the source location, using either the signal's envelopes [McCausland and Malone, 2004] or a modified beam-forming technique [Kao and Shan, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…[70] The five PBO sites B003, B004, B005, B007, and B018 are of special interest because they have recorded strain transients associated with the episodic tremor and slip ("ETS") episodes that appear to originate on the Cascadia subduction thrust at depths of 35 to 40 km [Dragert et al, 2001;Melbourne et al, 2005]. At these sites, the theoretical tidal strains are dominated by load tides from the Pacific Ocean and the Straits of Georgia and Juan de Fuca (Table 3).…”
Section: Northern Washington: Difficulty Matching Theoretical Tides Amentioning
confidence: 99%
“…Recent studies using GPS and high-density seismic networks extended the measurable period range to days, months and years, which led to the discovery of slow and silent earthquakes 8 . From early seismological studies, some earthquakes were known to be slow, with a timescale longer than a few minutes, but these recent studies demonstrated the existence of seismic events with even longer timescales, which are often associated with small tremors 9 .…”
Section: Slow and Silent Earthquakesmentioning
confidence: 99%